SIMULATION AND EXPERIMENTAL STUDIES ON HYDRODYNAMICS CHARACTERISTICS OF COCURRENT THREE PHASE FLUIDISATION USING FUZZY LOGIC (International Journal of Engineering and Computer Science, 2017)
Simulation and hydrodynamics studies were carried out in a solid - liquid - gas phase concurrent fluidized bed. The experiment was carried out in a 5.4cm I.D, 6cm O.D and 160cm height vertical Perspex column. Water was used as a continuous phase and air was used as a dispersed phase. Glass beads of diameter 0.2cm, 0.4cm, 0.6cm and Gypsum particle of diameter 0.1201cm, 0.1676cm, 0.2099cm were used as solid for concurrent studies. The column consists of three sections viz. gas liquid disengagement section, test section and gas liquid distributed section. The experiment was conducted with both Glass beads and Gypsum particles on keeping constant gas velocity by varying liquid velocities. The effect of individual phase holdup for various particle sizes with specific liquid flow rates and gas flow rates were studied. Pressure drop in the fluidized bed was measured by using mercury manometer. The individual phase holdups were determined, liquid holdup and solid holdup decreases with increase in liquid velocity whereas gas holdup increases with increases in liquid velocity. With the experimental data, simulation studies were carried out using Fussy Logic.